공공 및 민간부문의 사이버침해사고 현황분석에 따른 대응방안 - 조호대(Ho-Dae Cho); 신동일(Dong-Il Shin) (한국콘텐츠학회 논문지, 9(1), 2009)
We live was operates the life which is the Internet and became infra is very important. In order minimizes like this disfunction from will be applied the new order must take a position in cyber space. The cyber infringement most the information society brings about is serious concern middle one. The biggest thing is anonymous characteristic with cause of cyber crime. Also well cannot know becomes the cause where commits a crime that about cyber crime. Cyber crime the guilty conscience is thin. And the criminal who commits a cyber crime sense of insecurity is few. This paper which sees cyber infringement accident dividing came in public section, and analyzed presented a present condition and a confrontation plan. 우리가 살아가는데 있어서 인터넷이란 일상생활에서 없어서는 안 될 중요한 인프라가 되었다. 그러나 이러한 사이버 공간이 확장되고 일상화 되면서 여러 가지 역기능을 동시에 가져다주었다. 이러한 역기능을 최소화하기 위해서는 사이버공간에 적용될 새로운 질서가 정립되어야 한다. 사이버침해는 정보사회가 초래한 가장 심각한 문제 가운데 하나이다. 사이버 상에서는 상대방이 보이지 않으므로 그에 대한 죄의식이 희박하고 불안함도 적으며, 사이버 범죄의 처벌에 대한 무지도 생각할 수 있다. 본 연구에서는 공공부문과 민간부문에 대한 사이버침해정도를 알아보고, 공공부문과 민간부문의 사이버 침해현황을 분석하고 이를 바탕으로 사이버침해사고에 대한 대응방안을 제시하고자 한다.